HABITAT AND SPECIES SPECTRUM OF MYCOBACTERIA, ENVIRONMENTAL ISSUES MYCOBACTERIUM TUBERCULOSIS IN THE REPUBLIC OF DAGESTAN - R. A. Nuratinov; A. A. Sultanov; F. I. Islamova (Юг России: экология, развитие, 2014)
Studies have shown that mycobacteria persist in the body as pets and wild animals and birds. The largest number of isolated cultures assigned to groups II and III Runyon. From biomaterials sheep isolated culture M.bovis, and similar material from cattle - M.tuberculosis. Migration and persistence of pathogenic mycobacteria in non-specific host organisms defines them as additional sources of Mycobacterium tuberculosis to humans. Some importance in the spread of atypical mycobacteria may have pigeons, sparrows and field mice, it is important to consider in cases of paraalergicheskih reactions to tuberculin in cattle and small ruminants.